(untitled) (UNWE Yearbook, 2015)
Man, as a uniquely dualistic (spiritual and material) and cultural and political creature, has created three ‘eternal’ fundamental social structures for organization and governance of societies: State, Religion with its Church and Market (with its universal instrument – Money). These have been both in relationship of cooperation and interaction and in relationship of rivalry and struggle for domination and supremacy.Anti-spiritual market has turned out to be inadequate to Religion and Church, and al- most their enemy (Let us remember that hostility between them dates from ancient times, because already Christ expelled the merchants from the Temple). Market has also been declared incompatible with State and the need has been defined not only of a ‘Minimum State’, but of the full ‘absorption’ of State by it. It (market) transformed everything to subject of transaction and purchase and sale, including spiritual values and virtues; commercialized the political process and they began speaking of ‘political marketing’ and ‘power benefits. To L. Turow truth also appears to be the subject of market transaction, while О`Rourke – in the spirit of T. Hobbes, treats business, i.e. market, as ‘a modern version of war’. The phase ‘All is business, business is war’ was also ‘born’.Market is really ‘a great social mechanism of civilization’, but when it passes a definite critical point or degree in its development, it transforms from social welfare to social evil, i.e. a generator of anti-culture, a provocateur of conflicts, even instincts, or a source of ‘barbarization’ and ‘zoologizatio’ of the market subjects in the market society. The global financial and economic crisis has indicated and proven the need for transformation of neoliberal slogan-dilemma ‘Market or State?’ to the realistic and reasonable paradigm – ‘and Market, and State, and Morality (or Spirituality generally)’. Because (according to Immanuel Kant) without morality society will lose its human appearance and meaning.